Educational game based on macromedia flash in Indonesian language learning in junior high school - Putri , Ermira Nilansari; Etika Rahmawati, Laili; Sufanti, Main; Mansoor, Hafiza Sana (Universitas Ahmad Dahlan, 2023)
Educational Game is an application package that is used as a tool that aims to encourage students to undergo learning activities. The objectives of this study are (1) to describe educational games based on Macromedia Flash for Indonesian language learning in junior high schools; and (2) to describe the results of implementing Macromedia Flash-based educational games with the Fisher Yates Shuffle algorithm in learning Indonesian in junior high schools. The research approach is a qualitative descriptive research. The research is based on case studies with subjects and objects that focus on class VIIIC students and Indonesian language teachers at SMP Negeri 2 Jatisrono. Data collection techniques are by using observation techniques, questionnaires, interviews, and tests. The research sample is 30 VIIIC students. Data analysis is guided by Miles & Huberman's view which consists of three streams of activities that occur simultaneously, namely: data reduction, data presentation, drawing conclusions/verification. The data validity test was carried out using source triangulation technique. In connection with the research results based on eight indicators, it can be understood that the level of student activity in learning Indonesian based on educational games based on Macromedia Flash with the Fisher Yates Shuffle algorithm has increased. The percentage of 87% of students explained that the Macromedia Flash application based on the Fisher Yates Shuffle algorithm was able to increase student activity. This research encourages the integration of technology in the world of education. Flash-based games can offer interactive and dynamic content, enhancing the learning experience.